Assessing the Groundwater Recharge with Water Balance in Ameriat Al-Falluja City, Al-Anbar Governorate, Western Iraq - Alnoory, Marram Abd-alkdhium; Al-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2023)
This study aims to figure out how to calculate water recharge using the soil conservation service method, one of the most widely used methods for calculating runoff volume following rainfall. The research is being conducted in Ameriat Al-Falluja City, Al-Anbar Governorate. The Iraqi meteorological organization’s Baghdad Airport and Al-Ramadi stations provided data on the research area from 1989 to 2020 as total annual rainfall (123.1 mm), the RH% (43%), the mean monthly T (23.6 °C), total evaporation (3169.61 mm), the wind speed (3.1 m/s), and the sunshine duration (9 h/day). The climate of the study area is described as arid. The total evapotranspiration value quantity is 1137.38 mm for the 32-year comparison period, while the total amount of correct evapotranspiration was 992.3 mm. Water surplus is 36.7% of total rainfall, which equals 45.2 mm. Groundwater recharge is 45.2 mm, with a rate of 36.7%, showing the groundwater recharge (%) from total rainfall. The value of groundwater recharge throughout a year is about equivalent to 23.6848* 105 m3/year.